GVBD rate is an independent predictor for pregnancy in ICSI patients with surplus immature oocytes - Wang, Meng; Yang, Qiyu; Liu, Jing; Hu, Juan; Li, Dan; Ren, Xinling; Xi, Qingsong; Zhu, Lixia; Jin, Lei (Frontiers in Endocrinology, 2023)
It was reported that there were still up to 30% immature retrieved oocyte at germinal vesicle (GV) or metaphase I (MI) stage. Whether the spontaneous maturity competency of immature oocytes associated to the clinical outcome of in vitro fertilization (IVF) cycles remains unclear and unexplored. This study aimed to investigate How the oocyte developmental parameters in in vitro maturation (IVM) affect clinical outcomes of intracytoplasmic sperm injection (ICSI) cycles. This retrospective cohort study included couples undergoing ICSI in a university-affiliated hospital. Surplus immature oocytes during ICSI were collected and cultured in vitro. The numbers of germinal vesicle (GV) oocytes undergoing GV breakdown (GVBD) and polar body 1 extrusion within 24 h culture were recorded. The main outcome measurements were demographic baselines and oocyte developmental parameters in IVM associated with pregnancy outcomes. A total of 191 couples were included with an overall GVBD rate of 63.7 % (327/513) and oocyte maturation rate of 46.8 % (240/513). 53.4% (102/191) of them had embryos transferred freshly, which originated from metaphase II oocytes that matured spontaneously in vivo, and 60.8% (62/102) got pregnant. Among factors with a P-value < 0.2 in univariate logistic regression analyses of pregnancy correlation, GVBD rate (OR 3.220, 95% CI 1.060-9.782, P=0.039) and progesterone level on human chorionic gonadotropin (HCG) day (OR 0.231, 95% CI 0.056-0.949, P=0.042) remained significant in the multivariate model. The area under the curve (AUC) of the predictive nomogram was 0.729 (95% CI 0.632-0.826) with an acceptable calibration. Moreover, decision curve analyses illustrated the superior overall net benefit of models that included the GVBD rate in clinical decisions within a wide range of threshold probabilities. In conclusion, GVBD rate and progesterone level on HCG day may be associated with pregnancy outcomes in infertile couples during the regular ICSI procedure. An elevated GVBD rate within 24 h may greatly increase the likelihood of pregnancy in infertile couples during ICSI. This preliminary study may optimize clinical pregnancy prediction, which provides support in decision-making in clinical practice.